Application of Cloud Computing for The Development of Knowledge Management System Web Based Network - Chusnul Astri Ch; Rani Purbaningtyas; R Dimas Prasetyo (Fakultas Teknik Universitas Bhayangkara, 2017)
Developing Knowledge Management System using cloud computing is a concept that integrates knowledgemanagement (KM), with the process of finding, selecting, seeking, organizing and presenting data or information.KMS Network is a system that provides web-based content (contains data, information, & knowledge) as an increasein knowledge mastery, to help the needs of users or users who have difficulty when looking for sources of information.Kms is developed through the adoption of cloud computing (CC) technology, which has large amounts of data storageusing web servers or cloud servers online. In the research application of cloud computing for the development ofknowledge management system web-based network, has a speed in accessing the average article data 0.7833 seconds/ page, with the average page load memory 2.0 MB, search articles using the method